Sistem Pakar Diagnosa Tingkat Depresi Mahasiswa Tingkat Akhir Dengan Menggunakan Metode Certainty Factor - Nisrina Naufalia Santoso; Yani Maulita; Husnul Khair (Bulletin of Multi-Disciplinary Science and Applied Technology, 2022)
Changes in the learning environment can affect students' mental health so that students adapt forcefully. It is not only intelligence that determines success in learning, but peace of mind which also greatly influences the ability to use this intelligence. Mental health disorders or depression are more difficult to recognize and feel than physical health, resulting in a lack of awareness about mental health. An expert system is a branch of artificial intelligence that tries to imitate the reasoning process of an expert in solving problems. Where the expertise of this expert will make it easier for students to know the level of depression experienced and help find the right solution or treatment. Certainty Factor is one of the methods of an expert system that can see whether a fact is certain or uncertain and can provide accurate results obtained from the calculation of the weight of symptoms selected by experts and is able to provide answers to problems with uncertain results. Based on the results of the CF calculation, the highest value is in the type of major depression with a value of 0.721472 or 72.1472%. From the results obtained, the system identifies that the student has a type of severe depression. And the solution that can be done is to need special treatment for psychiatric problems.